PEMBERIAN SAYUR KACANG HIJAU (VIGNA RADIATA) UNTUK PENANGANAN ANEMIA PADA REMAJA PUTRI - Hasnawati Nukuhaly; Kasmiati Kasmiati; Arvicha Fauziah (Poltekkes Kemenkes Maluku, 2022)
The stage of growth and development of young women will be disrupted if anemia occurs. Anemia in adolescents is a problem that requires great attention because the incidence of anemia in adolescent girls is still very high, namely 72.3%. This study aims to determine the effect of giving green beans to increase hemoglobin levels in adolescent girls at UPT Paccing Health Center, City of Bone. The research method is quasi-experimental with a one group pretest and posttest design, sampling using accidental sampling technique where 30 samples of young women are obtained. This research uses a digital hemoglobin measuring device and an observation sheet. The research was carried out by giving 700 grams of green beans per day and then consumed in the form of green beans which were consumed for 18 days. The results of pre-post measurements showed that female adolescents whose hemoglobin was normal from 43.3% increased to 80%, those with mild anemia from 43.3% decreased to 20% while those with severe anemia were 13.3% to 0%. The results of the chi-square test showed that giving green beans to young women had an effect on increasing hemoglobin (p = 0.000). So that consuming green bean vegetables can be used as an alternative and prevention of the incidence of anemia in young women.